Pelaksanaan Fungsi Badan Permusyawaratan Desa di Kabupaten Barru: Analisis Faktor-Faktor yang Mempengaruhi - Hasan, Muddatsir; Muzakkir, Abd. Kahar (CV. Social Politic Genius (SIGn), 2024)
This research aims to examine the implementation of the Village Consultative Body’s functions in village governance within Barru Regency, as well as the factors influencing said implementation. Utilizing a quantitative descriptive approach, this empirical legal research was conducted in Barru Regency. Data were collected through questionnaires, documentation, and literature study. Quantitative data analysis techniques were used to analyze the research findings. The findings indicate that the implementation of the Village Consultative Body’s functions in village governance in Barru Regency, as mandated in Article 55 of Law Number 6 of 2014 jo. Article 31 of Ministerial Regulation Number 110 of 2016, has not yet been effectively executed. Several factors contribute to these shortcomings, including legal factors, legal culture, the adequacy of facilities and infrastructure, and the community factor. It is recommended that the Village Government implement capacity building programs for members of the Village Consultative Body, while simultaneously addressing these influencing factors. These steps are crucial to ensure the effective functioning of the Village Consultative Body in the administration of village governance in Barru Regency in the future.